“Enthusiasm, work, cooperation and intense brazilianity”: The early school agricultural clubs from Santa Catarina (1934-1938) - Elaine Aparecida Teixeira Pereira; Maria das Dores Daros (Tópicos Educacionais)
This article approaches the Clubes Agrícolas Escolares de Santa Catarina [School Agricultural Clubs from Santa Catarina] between 1934 and 1938, when the first initiatives were located, especially by the thematization of two of these associations: the Clube Agrícola Escolar Fritz Müller (from Garcia, Blumenau) and the Clube Agrícola Escolar from Colônia Oco (from Valões, Porto União). For this, it resorts to sources such as periodicals and reports and analyzes them based on the notion of repertoire, appropriated from the productions of Angela Alonso and Charles Tilly. The analyzes indicate that, despite starting from the same prescriptions and showing regularities in their ways of working, the Clubes Agrícolas Escolares studied also presented particularities and showed authorship in the uses of the prescribed.